Now you see her [compact disc, unabridged] : a novel - Patterson, James, 1947- (Hachette Audio, 2011)
Eighteen years ago, a terrible event forced Nina to leave her life in Florida behind and assume a new identity. Now a successful attorney in New York, Nina takes on a case that has unmistakable ties to her old life. To destroy old demons, she must return to Florida and confront her past.